Durability of Mortar Incorporating Ferronickel Slag Aggregate and Supplementary Cementitious Materials Subjected to Wet–Dry Cycles - Ashish Kumer Saha; Prabir Kumar Sarker (International Journal of Concrete Structures and Materials, 2018)
Abstract This paper presents the strength and durability of cement mortars using 0–100% ferronickel slag (FNS) as replacement of natural sand and 30% fly ash or ground granulated blast furnace slag (GGBFS) as cement replacement. The maximum mortar compressive strength was achieved with 50% sand replacement by FNS. Durability was evaluated by the changes in compressive strength and mass of mortar specimens after 28 cycles of alternate wetting at 23 °C and drying at 110 °C. Strength loss increased by the increase of FNS content with marginal increases in the mass loss. Though a maximum strength loss of up to 26% was observed, the values were only 3–9% for 25–100% FNS contents in the mixtures containing 30% fly ash. The XRD data showed that the pozzolanic reaction of fly ash helped to reduce the strength loss caused by wet–dry cycles. Overall, the volume of permeable voids (VPV) and performance in wet–dry cycles for 50% FNS and 30% fly ash were better than those for 100% OPC and natural sand.